Cardiovascular rehabilitation. Results in the cardiology service. - Juan José Navarro López; Roberto S. Vega Hernández.; Claudio González Rodríguez.; Teresa Rodríguez Rodríguez (Medisur)
Fundaments: Physical exercise produces changes in almost all the organism systems, the cardiovascular function is the main affected, important changes happen in the central heart bomb and in the outlying vasomotor regulation of the sanguine distribution. It has been demonstrated that the exercise favors modifications in the risk factors that comprises the lipídic patron, the glicemia, the overweight and some described more recently as the fibrinogen and the factors of the clotting. Objective : To analyze and to compare the effects of complex exercises in the patients included in the cardiovascular rehabilitation. Methods : Types study before and after, the total patients (30) included in the program of cardiovascular rehabilitation during 4 months in the Cienfuegos University Hospital ¨Dr. Gustavo Aldereguía Lima¨. Results : Out of the total of patient, 25 are males (83.3%), the diagnoses were: myocardium sharp attack, arterial hypertension with angina, myocardial revascularization and stable angina. In a highly significant way p < 0,0001 double product varied as much at the end of the jogging and the ergometric parameters: the maxim body burden reached, tolerated and the total time of exercise. In a significant way p < 0,001 varied the double product of the ergometric test and the units of the basal metabolism. Conclusions: For the clinical changes, ergometrics and psychological evaluated in those patients we can consider them integrally rehabilitated with this group of exercises.